Effect of income on the cumulative incidence of COVID-19: an ecological study - Ricardo de Mattos Russo Rafael; Mercedes Neto; Davi Gomes Depret; Adriana Costa Gil; Mary Hellem Silva Fonseca; Reinaldo Souza-Santos (Universidade de São Paulo, 2020)
Objective to analyze the relationship between per capita income and the cumulative incidence of COVID-19 in the neighborhoods of the city of Rio de Janeiro, RJ, Brazil. Method an ecological study using neighborhoods as units of analysis. The cumulative incidence rate per 100,000 inhabitants and the median of potential confounding variables (sex, race, and age) were calculated. Multiple analysis included quantile regression, estimating the regression coefficients of the variable income for every five percentiles from the 10th to 90th percentiles to verify the relationship between income and incidence. Results the city's rate was 36.58 new cases per 100,000 inhabitants. In general, the highest rates were observed in the wealthiest regions. Multiple analysis was consistent with this observation since the per capita income affected all percentiles analyzed, with a median regression coefficient of 0.02 (p-value <0.001; R2 32.93). That is, there is an increase of R$ 0.02 in the neighborhood's per capita income for every unit of incidence. Conclusion cumulative incident rates of COVID-19 are influenced by one's neighborhood of residency, suggesting that access to testing is uneven.